2010
DOI: 10.1152/ajpendo.00692.2009
|View full text |Cite
|
Sign up to set email alerts
|

Increased subsarcolemmal lipids in type 2 diabetes: effect of training on localization of lipids, mitochondria, and glycogen in sedentary human skeletal muscle

Abstract: Ørtenblad N. Increased subsarcolemmal lipids in type 2 diabetes: effect of training on localization of lipids, mitochondria, and glycogen in sedentary human skeletal muscle. Am J Physiol Endocrinol Metab 298: E706 -E713, 2010. First published December 22, 2009; doi:10.1152/ajpendo.00692.2009.-The purpose of the study was to investigate the effect of aerobic training and type 2 diabetes on intramyocellular localization of lipids, mitochondria, and glycogen. Obese type 2 diabetic patients (n ϭ 12) and matched o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
184
10
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(213 citation statements)
references
References 42 publications
(58 reference statements)
18
184
10
1
Order By: Relevance
“…T2DM is accompanied by perturbations to muscle physiology, resulting in decreased mitochondrial content and abnormal lipid deposition, impairing the insulin-mediated switch between fat and carbohydrate metabolism (37). Dietary nitrate supplementation exhibits anti-obesity and anti-diabetic properties in rodents; improving homeostatic model assessment for insulin resistance and quantitative insulin sensitivity check index assessments in high-fructose diet-induced insulin resistant rats (5), and improving glucose tolerance in NOS-deficient mice (4); while reducing adiposity in both models.…”
Section: Discussionmentioning
confidence: 99%
“…T2DM is accompanied by perturbations to muscle physiology, resulting in decreased mitochondrial content and abnormal lipid deposition, impairing the insulin-mediated switch between fat and carbohydrate metabolism (37). Dietary nitrate supplementation exhibits anti-obesity and anti-diabetic properties in rodents; improving homeostatic model assessment for insulin resistance and quantitative insulin sensitivity check index assessments in high-fructose diet-induced insulin resistant rats (5), and improving glucose tolerance in NOS-deficient mice (4); while reducing adiposity in both models.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known and well described that physical exercise training is perhaps the single best option for the prevention and treatment of T2DM. Nielsen et al (23) showed that a 10-week aerobic cycling training in obese, male T2DM patients and age-and BMI-matched controls indeed improved mitochondrial content (by ∼40 %) and that this was accompanied by an increase in insulin sensitivity in both groups. In 2010, we performed an exercise-training intervention in T2DM patients and BMI-and age-matched obese controls, and examined mitochondrial function in further detail.…”
Section: Mitochondria As a Target To Improve Insulin Sensitivitymentioning
confidence: 99%
“…We analysed lipid droplet density in two ways, counting (1) the number of lipid droplets in subsarcolemmal and intermyofibrillar regions normalised to muscle area and (2) the relative percentage of subsarcolemmal lipids. The latter was calculated by determining subsarcolemmal lipids normalised to muscle fibre surface area and intermyofibrillar lipids normalised to the volume beneath the surface area, assuming an average radius of 40 μm and cylindrical shape of the fibres as reported by others [5]. The cross-sectional area of individual lipid droplets was determined using a software package (iTEM; Olympus/SIS).…”
Section: Quantification Of Tem Imagesmentioning
confidence: 99%
“…These compartments also harbour subsarcolemmal and intermyofibrillar mitochondria, and therefore intramuscular lipid depots are found in close proximity to mitochondria [4]. Recently it has been suggested that the subcellular distribution of intramuscular lipid droplets in the subsarcolemmal region, rather than the total content of various lipid species, contributes to attenuation of insulin signalling in muscle [5]. There are several potential mechanisms that could result in subcellular variations in intramuscular lipid accretion, including regionally selective impairments of mitochondrial fatty acid oxidation and/or increased abundance of the enzymes involved in triacylglycerol esterification.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation